Causal effects of early career sorting on labor and marriage market choices: A foundation for gender disparities and norms - Itzik Fadlon; Frederik Plesner Lyngse; Torben Heien Nielsen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
We study whether and how early labor market choices determine longer-run career versus family outcomes differentially for male and female professionals. We analyze the physician labor market by exploiting a randomized lottery that determines the sorting of Danish physicians into internships across local labor markets. Using administrative data spanning ten years after physicians' graduations, we find causal effects of early-career sorting on a range of life cycle outcomes that cascade from labor market choices, including human capital accumulation and occupational choice, to marriage market choices, including matching and fertility. The persistent effects are entirely concentrated among women, whereas men experience only temporary career disruptions. The evidence points to differential family-career tradeoffs and the mentorship employers provide as channels underlying this gender divergence. Our findings have implications for policies aimed at gender equality in outcomes, as they reveal how persistent gaps can arise even in institutionally gender-neutral settings with early-stage equality of opportunity.
Keywords: 330; Berufswahl; Wirkungsanalyse; Ehe; Familie-Beruf; Erwerbsverlauf; Geschlechterrolle; Geschlechterunterschiede; Weibliche Arbeitskräfte; Ärzte; Dänemark